83.5k views
2 votes
You have two exponential functions. One function has the formula g(x) = 3(2 x ). The other function has the formula h(x) = 2 x+1. Which option below gives formula for k(x) = (g – h)(x)?

A) k(x) = 2x
B) k(x) = 5(2x)
C) k(x) = 5(2x+1)
D) k(x) = 2

2 Answers

1 vote

Your Answer Would Be:

k(x)=2^x

User Sidpat
by
5.5k points
6 votes
Given two exponential functions:

g(x)=3(2^x) and
h(x)=2^(x+1)


k(x) = (g-h)(x) is given by

k(x)=g(x)-h(x) \\ \\ =3(2^x)-2^(x+1)=3(2^x)-2(2^(x)) \\ \\ =2^x(3-2)=2^x

Therefore, the option that gives the formula for k(x) = (g - h)(x) is option A.

k(x)=2^x
User Tsbertalan
by
6.5k points